Prime Minister Decree No. 2873 of the year 2015 Regarding the Committee of Experts Responsible for Examining Reconciliation and Settlement Requests in Crimes of Misappropriation of Public Funds, and its Technical Secretariat = قرار رئيس مجلس الوزراء رقم 2873 لسنة 2015 بشأن لجنة الخبراء المختصة بنظر طلبات التصالح والتسوية وأمانتها الفنية فى جرائم العدولن على المال العام - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic